Direct Writing of Additive‐Free MXene‐in‐Water Ink for Electronics and Energy Storage. Issue 1 (5th September 2018) - Quain, Evan; Mathis, Tyler S.; Kurra, Narendra; Maleski, Kathleen; Van Aken, Katherine L.; Alhabeb, Mohamed; Alshareef, Husam N.; Gogotsi, Yury
Abstract: Additive‐free, single step formulations of MXene‐in‐water inks are developed from clay‐like titanium carbide (Ti3 C2 ) sediments. Solution‐processable Ti3 C2 inks are compatible with stamping, printing, painting, and writing on a variety of substrates. Specifically, MXene‐in‐water inks at higher concentrations of 30 mg mL −1 are employed in commercially available pens for dispensing and patterning 2D MXene directly. These MXene pens are employed either manually or automatically using an AxiDraw, enabling direct‐writing and complex patterning of functional MXene devices. Versatile MXene pens show compatible writing on a variety of substrates, including paper and polymers, where the deposited ink is used as a passive circuit, similar to silver and copper nanoparticle inks. Written MXene lines without additional post‐treatment exhibit length dependent resistance, showing typical resistivity values between carbon based and metal nanoparticle inks. Current collector‐free fabrication of MXene micro‐supercapacitors is demonstrated on unconventional platforms including paper, textiles, and curved surfaces directly. Abstract : Rollerball pen uses MXene‐in‐water ink for writing passive and active components directly on printing paper. Conductive MXene forms electrical conduits and planar supercapacitors in a single step without postprocessing.